2011
DOI: 10.1007/s13593-011-0040-2
|View full text |Cite
|
Sign up to set email alerts
|

A meta-analysis of long-term effects of conservation agriculture on maize grain yield under rain-fed conditions

Abstract: Conservation agriculture involves reduced tillage, permanent soil cover and crop rotations to enhance soil fertility and to supply food from a dwindling land resource. Recently, conservation agriculture has been promoted in Southern Africa, mainly for maize-based farming systems. However, maize yields under rain-fed conditions are often variable. There is therefore a need to identify factors that influence crop yield under conservation agriculture and rain-fed conditions. Here, we studied maize grain yield dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
260
3
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 394 publications
(303 citation statements)
references
References 103 publications
18
260
3
3
Order By: Relevance
“…In some environments the benefits of CA started after 1-2 seasons, whereas in other environments the benefits required more seasons for effects to build up 23,94 , which is in agreement with a recent meta-analysis 96 . For example, in the high-rainfall environment of Zidyana EPA, Malawi, characterized by sandy loam soils, substantial maize yield benefits were obtained after five seasons 28 .…”
Section: Effects Of Ca On Productivitysupporting
confidence: 90%
See 1 more Smart Citation
“…In some environments the benefits of CA started after 1-2 seasons, whereas in other environments the benefits required more seasons for effects to build up 23,94 , which is in agreement with a recent meta-analysis 96 . For example, in the high-rainfall environment of Zidyana EPA, Malawi, characterized by sandy loam soils, substantial maize yield benefits were obtained after five seasons 28 .…”
Section: Effects Of Ca On Productivitysupporting
confidence: 90%
“…However, these past researches were largely conducted within experimental stations and did not take into account socio-economic constraints in real farm situations that could hinder the widespread adoption of CA. Recently, more studies reporting results from onfarm and on-station trials have been published concentrating on some of the above-mentioned challenges and constraints 28,37,68,73,86,94,96,97,99,101,102,104,[113][114][115][116] .…”
Section: Constraints To Adoption Of Ca Systems In Southern Africamentioning
confidence: 99%
“…However in rest of treatment combinations of management practice and tillage there was increase in yield from first year to third year respectively. The most astonished results was obtained under control treatment in which the yield decline from first year to third year was 800% and no yield was reported in third year, the results are corroborated by the findings of Rusinamhodzi et al (2011). It might be due to fact that due to non application of any source of nutrient(organic and inorganic) the pathogens mainly fungus attack the plant root and used as source of nutrients causes decline and no yield.…”
Section: Specific Nitrogenase Activitysupporting
confidence: 64%
“…been in place (Rusinamhodzi et al, 2011). Results of other studies have also suggested a crop, soil, and general location specifi c yield benefi t from NT compared with CT for sorghum, wheat, and other crops in the United States, specifi cally in the Great Plains region (Norwood et al, 1990;Norwood, 1992;Unger, 1994;Schlegel et al, 1999;Toliver et al, 2012;Farooq et al, 2011).…”
Section: Core Ideasmentioning
confidence: 99%